A Pragma-Dialectical Approach to Trade Friction Discourse: A Case Study of a Public Letter in Sino-US Trade Friction on Tire Special Safeguard - Peng, Wu; Rui, Zhao (Sinología hispánica. China Studies Review, 2016)
Based on the analytical framework of Strategic Maneuvering, this paper analyzes and evaluates the public letter from China Chamber of Commerce of Metals, Minerals & Chemicals Importers & Exporters (CCCMC) and China Rubber Industry Association (CRIA) to Obama and United States Trade Representative (USTR) on July 27th, 2009 to reveal the discursive strategies and their corresponding linguistic realizations manipulated in tire special safeguard case. The research results show that, strategic maneuvering in CCCMC & CRIA’s public letters is integratedly realized through choice of topical potential, catering for audience demands and choice of presentational devices, which is supported by such argumentative strategies as presupposition, contrast, appeal to audience’s values, appeal to authority, vagueness, repetition, statistics, appeal to opponent ’ s concession, and the like. CCCMC & CRIA’s public letter has its shortcomings in clarification of difference of opinion in the confrontation stage, in choice of starting in the opening stage, in choice of topics in the argumentation stage and in manipulation of such specific argumentativerhetoric strategies as ‘contrast’ and ‘statistics’. In view of China’s merits and deficiency, China should: (1) clarify the confrontation, opening, argumentation and concluding stages of the argumentative discourse and flexibly set the dialectic and rhetoric aims of these four stages according to the context; (2) strategically maneuver among topical potential, audience demand and presentational devices, in line with the established dialectic and rhetoric aims in different argumentative stages; (3) recognize the institutional context of trade friction discourse and the importance of language expression, and cultivate an assertive image.